A case series of hypersensitivity reactions to ventriculoperitoneal shunt material. (September 2021) - Lanlokun, Mosopefoluwa A.; Guerriero, Emily; Friedlander, Robert M.; Fajt, Merritt L.
Highlights: Hypersensitivity reactions to ventriculoperitoneal shunts are rare. Both standard and hypoallergenic (silicone-free) shunts can cause reactions. Shunt allergy can manifest with a pruritic, erythematous rash. Patch testing to shunt material can assist in the diagnosis. Abstract: Hypersensitivity reactions to ventriculoperitoneal (VP) or lumboperitoneal (LP) shunts are rare. Symptoms often resolve following shunt replacement with a silicone-free hypoallergenic shunt. We describe novel cases of allergies to both standard and hypoallergenic shunts and highlight the utility of patch testing. Patient 1, a 24-year-old female with Chiari I malformation, developed diarrhea, abdominal pain, and rash along the LP shunt tract. Patch testing was positive. The shunt was replaced with a hypoallergenic VP shunt with symptom improvement. Five weeks later, she developed a new rash. Subsequent patch testing to the hypoallergenic shunt was positive. Patient 2, a 37-year-old female with Chiari I malformation, developed pruritus along the VP shunt tract. Patch testing to the standard shunt was positive. The shunt was replaced with a hypoallergenic shunt, with symptomatic improvement. One month later, she developed neck pain, headache, and pruritis. Patch testing to the hypoallergenic shunt was positive. The development of a pruritic rash along the shunt tract with or without gastrointestinal symptoms should prompt shunt allergy evaluation and consideration of patch testing to the shunt material.